An Analysis of the Darkest Part of the Forest by Holy Black in Light of Wendy B. Faris’ Model of Narrative Techniques in Magical Realism - Bushra Munawar; Hina Rafique; Huma Amin (NUST Journal of Social Sciences and Humanities)
This research study focuses on the analysis of the narrative techniques of the text The Darkest Part of the Forest by Holy Black, an American novelist, in light of Wendy. B. Faris’ theory of narrative techniques in magical realism proposed in Ordinary Enchantment: Magical Realism and the Remystification of Narrative (2004) that serves as theoretical framework. In this context, the present research is a post-modernist analysis of the text since magical realism is mode of writing under Post Modernism. The study negotiates that text appears as a magical realist text because it shows several instances, settings, plot and characters which present it more than a fantasy. The plot revolves around the horned boy, a faerie prince, faeries, their encounter with human beings, magic, spell, and pastoral settings. The analysis of juxtaposition of realistic elements with fantasy or unrealistic happenings is the focus of this research. Wendy B. Faris has proposed five primary elements as the narrative building blocks of the binary opposition between realism and fantasy: the irreducible element, unsettling doubts, the phenomenal world, merging realms and, the distortion of time, space and identity. The researchers’ aim is to investigate whether Faris’ five elements may be successfully applied to the text under analysis. The findings of this research study amplify that this text is a post-modernist piece of writing and it truly exhibits the amalgamation of fantasy and real word occurrences. By discerning narrative elements in the text through discussion and textual references, the researchers have negotiated how these narrative elements served as building blocks of magical realism in the selected text. This research is qualitative and descriptive and adds to the body of Fantasy, American and Post-Modernist literature.